Leveraging a collaborative consortium model of mentee/mentor training to foster career progression of underrepresented postdoctoral researchers and promote institutional diversity and inclusion. - Laurie E Risner; Xenia K Morin; Evelyn S Erenrich; Philip S Clifford; Jeffrey Franke; Imogen Hurley; Nancy B Schwartz (PLoS ONE)
Changing institutional culture to be more diverse and inclusive within the biomedical academic community is difficult for many reasons. Herein we present evidence that a collaborative model involving multiple institutions of higher education can initiate and execute individual institutional change directed at enhancing diversity and inclusion at the postdoctoral researcher (postdoc) and junior faculty level by implementing evidence-based mentoring practices. A higher education consortium, the Big Ten Academic Alliance, invited individual member institutions to send participants to one of two types of annual mentor training: 1) "Mentoring-Up" training for postdocs, a majority of whom were from underrepresented groups; 2) Mentor Facilitator training-a train-the-trainer model-for faculty and senior leadership. From 2016 to 2019, 102 postdocs and 160 senior faculty and administrative leaders participated. Postdocs reported improvements in their mentoring proficiency (87%) and improved relationships with their PIs (71%). 29% of postdoc respondents transitioned to faculty positions, and 85% of these were underrepresented and 75% were female. 59 out of the 120 faculty and administrators (49%) trained in the first three years provided mentor training on their campuses to over 3000 undergraduate and graduate students, postdocs and faculty within the project period. We conclude that early stage biomedical professionals as well as individual institutions of higher education benefited significantly from this collaborative mentee/mentor training model.